Pengembangan Penerimaan Peserta Didik Baru berbasis Website dengan Menggunakan Metode Waterfall (Studi Kasus SLBN 1 Palangka Raya) - Bayu Eka Daman Puri Widodo; Satrio Agung Wicaksono; Faizatul Amalia (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
SLBN 1 Palangka Raya is a school that follows technological developments to date. To keep up with current technological developments, the school has developed a website-based media to facilitate the management of new students who register at SLBN 1 Palangka Raya. Website development was developed using the waterfall method, which was chosen because the development process is easy to manage and the steps are systematic. The development process in research begins with interviews, to find out what the needs of the new student admissions website will be. The data obtained in the next step is used to develop the next stage of the process, namely activity diagrams, sequence diagrams, class diagrams, and interface design. The implementation phase is where the algorithm is implemented according to the requirements analysis and design developed previously. The last step is testing with BlackBox testing and user acceptance testing methods used. From the results of testing the system using BlackBox testing which was tested with 29 test cases carried out using two user accounts, namely admin and students, the results of the system that was made could run well according to the needs and functionalities that had been designed at the planning stage. The PPDB website that has been implemented has also been tested for user acceptance by giving a questionnaire to get appropriate results from three criteria, namely Functional Correctness, and Completeness, usability, and Data Conversion, which is given to the new student admissions committee as admin, and also to prospective students who represented by one of the new students at SLBN 1 Palangka Raya. The results obtained from the user acceptance test, the answers to all questions get a percentage of 100% to agree which of the users, namely admin and students answered "YES" in the distributed questionnaire, it can be concluded that these results make the system well received and used by users.